Satellite‐Observed Major Greening and Biomass Increase in South China Karst During Recent Decade. Issue 7 (16th July 2018) - Brandt, Martin; Yue, Yuemin; Wigneron, Jean Pierre; Tong, Xiaowei; Tian, Feng; Jepsen, Martin Rudbeck; Xiao, Xiangming; Verger, Aleixandre; Mialon, Arnaud; Al‐Yaari, Amen; Wang, Kelin; Fensholt, Rasmus
Abstract: Above‐ground vegetation biomass is one of the major carbon sinks and provides both provisioning (e.g., forestry products) and regulating ecosystem services (by sequestering carbon). Continuing deforestation and climate change threaten this natural resource but can effectively be countered by national conservation policies. Here we present time series (1999–2017) derived from complementary satellite systems to describe a phenomenon of global significance: the greening of South China Karst. We find a major increase in growing season vegetation cover from 69% in 1999 to 81% in 2017 occurring over 1.4 million km 2 . Over 1999–2012, we report one of the globally largest increases in biomass to occur in the South China Karst region (on average +4% over 0.9 million km 2 ), which accounts for 5% of the global areas characterized with increases in biomass. These increases in southern China's vegetation have occurred despite a decline in rainfall (−8%) and soil moisture (−5%) between 1999 and 2012 and are derived from effects of forestry and conservation activities at an unprecedented spatial scale in human history ( 20, 000 km 2 yr −1 since 2002). These findings have major implications for the provisioning of ecosystem services not only for the Chinese karst ecosystem (e.g., carbon storage, water filtration, and timber production) but also for the study of global carbon cycles. Key Points: We find one of the globally largest increases in vegetation cover and above‐ground biomass to occur in South China Karst We apply a new Earth observation system based on low frequency passive microwaves to monitor biomass dynamics The increase in vegetation cover (69% in 1999; 81% in 2017) occurs over 1.4 million km 2 and has been generated by widespread conservation efforts